2007
DOI: 10.1097/bcr.0b013e318159bfbb
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Adrenal Insufficiency in Severely Injured Burn Patients

Abstract: Acute adrenal insufficiency (AI) is an uncommon disorder among critically ill burn patients, which can often go unrecognized. The goal of the current study is to identify risk factors for AI among patients who have sustained severe thermal injury. A case-control study was conducted among all adult patients admitted to the intensive care unit of the University of Alabama at Birmingham Burn Center during a 7-year period (1997-2003). All burn patients who developed AI were selected as cases (n = 26), and a random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Those with massive burns have higher cortisol levels but may be resistant to serum cortisol increases in response to stimulation. The clinical relevance of this finding has not been established (81,82).…”
Section: Preventable Complicationsmentioning
confidence: 84%
“…Those with massive burns have higher cortisol levels but may be resistant to serum cortisol increases in response to stimulation. The clinical relevance of this finding has not been established (81,82).…”
Section: Preventable Complicationsmentioning
confidence: 84%
“…Reiff et al found higher % TBSA (total body surface area) and older age to be risk factors for acute adrenal insufficiency in severely burned patients by case-control study [9].…”
Section: Discussionmentioning
confidence: 99%
“…The issue is central to the concept of adrenal insufficiency in the critically ill, but is clearly a difficult one to address. The pattern of a reduced cortisol increment can be observed in a number of other conditions apart from sepsis; these include head injury, trauma and burns, which may suggest that it is a general response to critical illness. At present, the evidence that treating patients with septic shock and a reduced cortisol increment results in an improved outcome is contentious.…”
Section: Controversiesmentioning
confidence: 99%